ETV in infancy and childhood below 2 years of age for treatment of hydrocephalus - El Damaty, Ahmed; Marx, Sascha; Cohrs, Gesa; Vollmer, Marcus; Eltanahy, Ahmed; El Refaee, Ehab; Baldauf, Joerg; Fleck, Steffen; Bächli, Heidi; Zohdi, Ahmed; Synowitz, Michael; Unterberg, Andreas; et al. (Child's nervous system, 2020)
Age and etiology play a crucial role in success of endoscopic third ventriculostomy (ETV) as a treatment of obstructive hydrocephalus. Outcome is worse in infants, and controversies still exist whether ETV is superior to shunt placement. We retrospectively analyzed 70 patients below 2 years from 4 different centers treated with ETV and assessed success.
Gesehen am 18.10.2021